Outside the Magic Circle of White Male Supremacy in the Jim Crow South: Virginia Foster Durr’s Memoirs - Jiménez-Placer, Susana María (Text Matters: A Journal of Literature, Theory and Culture, 2018)
Virginia Foster Durr was born in 1903 in Birmingham, Alabama in a former planter class family, and in spite of the gradual decline in the family fortune, she was brought up as a traditional southern belle, utterly subjected to the demands of the ideology of white male supremacy that ruled the Jim Crow South. Thus, she soon learnt that in the South a black woman could not be a lady, and that as a young southern woman she was desperately in need of a husband. It was not until she had fulfilled this duty that she began to open her eyes to the reality of poverty, injustice, discrimination, sexism and racism ensuing from the set of rules she had so easily embraced until then. In Outside the Magic Circle, Durr describes the process that made her aware of the gender discrimination implicit in the patriarchal southern ideology, and how this realization eventually led her to abhor racial segregation and the ideology of white male supremacy. As a consequence, in her memoirs she presents herself as a rebel facing the social ostracism resulting from her determination to fight against gender and racial discrimination in the Jim Crow South. This article delves into Durr’s composed textual self as a rebel, and suggests the existence of a crack in it, rooted in her inability to discern the real effects of white male supremacy on the domestic realm and in her subsequent blindness to the reality behind the mammy stereotype.